The Role of Education in Livelihoods in the Somali Region of Ethiopia - Jackson, Elanor (Tufts Archival Research Center, 2005)
This report seeks to understand people's perceptions of the past and future role of education in the livelihoods of people in the Somali Region of Ethiopia, including the livelihoods of pastoralists, of those exiting pastoralism and those seeking to diversify their livelihoods.